Virtual Embodiment Using 180° Stereoscopic Video - Landau, Daniel H.; Hasler, Béatrice S.; Friedman, Doron (Frontiers in Psychology, 2020)
One of the most exciting possibilities of virtual reality is inducing in participants the illusion of owning a virtual body. This has become an established methodological paradigm allowing to study the psychological and neural correlates of various scenarios that are impossible in the real world, such as gender or age switching. Thus far, full-body ownership illusions have been implemented by using real-time body tracking and avatars based on computer-generated imagery (CGI). We propose an alternative technique to induce perceived ownership over a (photorealistic) virtual body using 180º stereoscopic video, synchronous touch, and narration. We describe the technical components of our novel technique and an example implementation as part of a science-art project that enables participants to experience virtual bodies of different ages, and present the results of an experimental evaluation study based on this experience. Consistent with previous virtual embodiment studies using CGI-based techniques, we found that participants accept a photorealistic virtual body as their own irrespective of its appearance as indicated by similar ratings of the strength of body ownership over a virtual body of a child versus an adult. We further show that our novel technique can alter participants’ cognition in accordance with the characteristics of their virtual body. Specifically, young adult participants who were embodied in the virtual body of a child significantly overestimated the duration of the virtual reality experience compared to a control group who was embodied in a virtual body of their own age. This finding corresponds to chronological age differences in time estimations and extends previous research on virtual child embodiment. Overall, these findings provide initial evidence for the potential of our novel technique to create photorealistic embodiment experiences with comparable psychological effects as have been found using CGI-based techniques while reducing the costs and technical complexity in the production and application of virtual body ownership illusions.